2022
DOI: 10.3389/fped.2022.828297
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork and Adherence to Guideline on Newborn Resuscitation—Video Review of Neonatal Interdisciplinary Teams

Abstract: BackgroundLittle is known about the importance of non-technical skills for the adherence to guidelines, when teams of midwives, obstetricians, anesthesiologists, and pediatricians resuscitate and support the transition of newborns. Non-technical skills are competences underpinning successful teamwork in healthcare. These are usually referred to as leadership, situational awareness, communication, teamwork, decision making, and coping with stress and fatigue.ObjectiveBy review of videos of teams managing newbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…This calls for rethinking our learning path for vacuum extraction, ensuring that trainees learn to include effective teamwork behavior in training and practice. Thus, this study confirms the results on surgical (30), trauma (31,32), and resuscitation teams (33)(34)(35) regarding the importance of non-technical skills in providing high clinical performance. Clinical performance and non-technical skills.…”
Section: Discussionsupporting
confidence: 86%
“…This calls for rethinking our learning path for vacuum extraction, ensuring that trainees learn to include effective teamwork behavior in training and practice. Thus, this study confirms the results on surgical (30), trauma (31,32), and resuscitation teams (33)(34)(35) regarding the importance of non-technical skills in providing high clinical performance. Clinical performance and non-technical skills.…”
Section: Discussionsupporting
confidence: 86%
“…This study only identified technical skills to be included in a SBT curriculum. However, excellent use of non-technical skills has been shown to improve clinical performance [23], and it is essential to include such skills when designing SBT courses. Whereas this study aimed to identify technical skills that should be included in a simulation-based curriculum in neonatology, most training occurs in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Teamwork is the key to resuscitation in a real clinical setting, and it could be improved through briefing and debriefing [ 48 , 49 ]. During a debriefing, the leader should identify strengths and weaknesses in a positive forum, where everyone understands that the only goal is to enhance future performance.…”
Section: Discussionmentioning
confidence: 99%